Impact of feed optimization and extension intervention on productive and reproductive performance in commercial dairy farms of urban areas in the eastern region of Ethiopia - Senbeta, Ewonetu Kebede; Zeleke, Negassi Ameha; Dingidie, Gemechu Taffa (Indian Journal of Dairy Science, 2021)
This study aimed at assessing the husbandry practices and evaluates the impact of feed optimization on productive performances and reproductive disorders of dairy cows. The study was conducted in purposefully selected Harar and Dire Dawa cities on 76 and 16 dairy farms respectively. Data were collected by use of semi-structured questionnaires and focused group discussion. Commonly used feeds were analyzed for their nutrition and standardized to the cows’ requirement. Milk yield was recorded every day for four consecutive months while milk composition was evaluated every month. Data analysis was done by SPSS, one-way ANOVA and t-Test. The pre-intervention results showed that farmers from small, medium and large-scale farms fed cows on low concentrate quantity of 3.76, 4.61 and 5.84Kg/day, respectively. The quantity of concentrate supplementation per cow per day was significantly different (p